Population Evacuation Need Assessment in Cyclone Affected Barguna District - Tamima, Umma (Journal of Bangladesh Institute of Planners, 2012)
Spatial difference in geophysical risk and social vulnerability presents challenges to emergency planners to develop an effective evacuation strategy for cyclone zones. This study examines spatial variability in evacuation assistance needs during cyclone hazard in Barguna district. For this, composite vulnerability map of unions in Barguna district is developed based on the community demographics, resources, structures and geophysical risk indicators. Four evacuation dimensions are analyzed based on population traits and building structures index, differential access to resources index, special evacuation needs index and a combination of three dimensions. Results indicate that relative majority of the unions are characterized by high evacuation assistance need and similar scenario exists in the spatial distribution of geophysical risk and socio-economic vulnerability. Nevertheless, spatial disparity of socioeconomic vulnerability is also observed among the unions within the geophysical risk zone. The coastal unions of Barguna districts are identified as the geophysical risk zone of which Raihanpur, Bardarkhali, Keorabunia, Burir Char, Amtali, Haldia, Arpagashia, Barguna, Dhalua, Kakchira, Nachnapara, Kantaltali, Char Duanti, Kalmegha, Patharghata, Barabagi, Karaibaria, Pancha Karalia, Naltona, and Baliatali unions are within the high geophysical risk zone. Furthermore, depending on the indices it is revealed that 72.26 percent people are living within the geophysical risk zone, while 17.72 percent and 47.42 percent people are living within the high and medium socio-economic vulnerable regions respectively. Thus this study finds out that about 65.14 percent people of Barguna district require evacuation assistance needs. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9575 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 145-157